Preservation of Community Values: Study of the Samin Bojonegoro Teaching Transformation Model Through the Education Unit Curriculum - Sulanam, Sulanam; Huda, Muhammad Nuril (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
This article explains the process of instilling values, which is carried out by internalizing community teachings through educational units. The internalization of values is achieved by inserting Samin's noble pitutur in PAI and PPKn subjects at elementary, middle and high school levels. The choice of this educational institution indicates that schools have a strategic role in preserving values. This participatory action research was conducted in Dusun, Japan, a hamlet inhabited by the Samin Bojonegoro community. This community adheres to the teachings of its ancestors. However, on the other hand, the openness in this community also allows for a permissive attitude, which has the potential to erode the strength of their traditions. The research was carried out for four months, starting with problem mapping, problem analysis and action involving traditional stakeholders, policy stakeholders and education stakeholders. The choice of action taken is to insert community values through Islamic Religious Education and Character subjects and Pancasila and Citizenship Education subjects. This insertion is a cultural preservation strategy that stakeholders consider to be the right step because, through this institution, children can internalize the noble values that exist around them.